Adsorption and photocatalytic behavior of titanate nanotubes sensitized with zinc tetra(4-carboxyphenyl) porphyrin. Issue 42 (9th April 2015) - Wang, Huigang; Fu, Ying; Han, Tiehu; Wan, Junmin; Zheng, Xuming
Abstract : Effect of calcination temperature and ZnTCPP sensitizer on the morphology of ZnTCPP–TNTS. Abstract : Titanate nanotubes sensitized with zinc tetra(4-carboxyphenyl) porphyrin (ZnTCPP–TNTS) were synthesized via the hydrothermal treatment of ZnTCPP–TiO2 gel and the photogenerated reactive species, holes and electrons were studied by transient absorption spectroscopy. The recombination of holes and electrons in the ZnTCPP–TNTS was of the order of picoseconds as a result of the ultra-fast free electrons. The time-correlated single-photon counting technique combined with confocal fluorescence microscopy revealed that the fluorescence intensity of ZnTCPP was dramatically weakened and the fluorescence lifetime under UV excitation was shortened by the TNTS. The specific surface area of the prepared ZnTCPP–TNTS reached 335.3 m 2 g −1 as determined by the N2 adsorption–desorption isotherms and the specific surface area decreased as the temperature of calcination increased. The products were characterized by TEM, SEM and XRD. The adsorption and photocatalysis of methylene blue over the ZnTCPP–TNTS were systematically investigated. The sorption kinetics of methylene blue can be described by a pseudo-second-order model and the thermodynamics fitted well with the monolayer Langmuir adsorption isotherm model. The high specific surface area, two-fold absorbent properties and easy separation of the ZnTCPP–TNTS for recycling show promising prospects for the treatment of dye pollutants from waste waters in industrial applications.